A two-stage Failure Mode and Effect Analysis of offshore wind turbines - Li, He; Teixeira, Angelo P.; Guedes Soares, C. (Renewable energy, 2020)
This paper proposes a two-stage Failure Mode and Effect Analysis (FMEA) technique as a basis for implementing the failure analysis of offshore wind turbines. At the first stage, critical failure causes and failure modes of each component of offshore wind turbines are identified. In the next stage, critical components and systems of offshore wind turbines are ascertained by a cost-and-risk-based index that considers both risk priority and failure costs of components. The objective is to overcome some weaknesses of the traditional FMEAs including: (i) Risk-based FMEA ignores practical information extracted in the operation stage of offshore wind turbines such as failure cost and, (ii) Cost-based FMEA addresses mainly failures of components and systems and cannot deepen to failure modes and failure causes of offshore wind turbines. A methodology towards conducting uncertainty analysis of FMEA results is developed to provide a new insight into a good understanding of FMEAs and their results. The developed uncertainty analysis methodology reveals that the proposed two-stage FMEA technique is adequate to reduce the uncertainty of FMEA results and is superior in failure analysis of offshore wind turbines. The application of the methodology can provide recommendations toward corrective actions and condition-based maintenance implementations. •A two-stage (FMEA) technique is proposed as a basis for implementing failure analysis of offshore wind turbines.•First stage, critical failure causes and failure modes of each component of offshore wind turbines are identified.•Next stage, critical components and systems of offshore wind turbines are ascertained by a cost-and-risk-based index.•A methodology towards conducting uncertainty analysis of FMEA results is developed.•The methodology can lead towards correction actions and condition-based maintenance implementation.